On the role of monetary incentives in risk preference elicitation experiments - Andreas Hackethal; Michael Kirchler; Christine Laudenbach; Michael Razen; Annika Weber (Leibniz Institute for Financial Research SAFE, 2021)
Incentivized experiments in which individuals receive monetary rewards according to the outcomes of their decisions are regarded as the gold standard for preference elicitation in experimental economics. These task-related real payments are considered necessary to reveal subjects' rue preferences". Using a systematic, large-sample approach with three subject pools of private investors, professional investors, and students, we test the effect of task-related monetary incentives on risk preferences in four standard experimental tasks. We find no systematic differences in behavior between and within subjects in the incentivized and non-incentivized regimes. We discuss implications for academic research and for applications in the field.
Keywords: C91; D01; D81; 330; Risk Preferences; Incentives; Experimental Economics; Risk Aversion